Sleep and diabetes‐specific psycho‐behavioral outcomes of a new automated insulin delivery system in young children with type 1 diabetes and their parents. Issue 3 (8th December 2020) - Bisio, Alessandro; Brown, Sue A; McFadden, Ryan; Pajewski, Michael; Yu, Pearl L; DeBoer, Mark; Schoelwer, Melissa J; Bonner, Heather G; Wakeman, Christian A; Cherñavvsky, Daniel R; Gonder‐Frederick, Linda
Abstract: Background: Data on the use of Control‐IQ, the latest FDA‐approved automated insulin delivery (AID) system for people with T1D 6 years of age or older is still scarce, particularly regarding nonglycemic outcomes. Children with T1D and their parents are at higher risk for sleep disturbances. This study assesses sleep, psycho‐behavioral and glycemic outcomes of AID compared to sensor‐augmented pump therapy (SAP) therapy in young children with T1D and their parents. Methods: Thirteen parents and their young children (ages 7–10) on insulin pump therapy were enrolled. Children completed an initial 4‐week study with SAP using their own pump and a study CGM followed by a 4‐week phase of AID. Sleep outcomes for parents and children were evaluated through actigraphy watches. Several questionnaires were administered at baseline and at the end of each study phase. CGM data were used to assess glycemic outcomes. Results: Actigraphy data did not show any significant change from SAP to AID, except a reduction of number of parental awakenings during the night ( p = 0.036). Parents reported statistically significant improvements in Pittsburgh Sleep Quality Index total score ( p = 0.009), Hypoglycemia Fear Survey total score ( p = 0.011), diabetes‐related distress ( p = 0.032), and depression ( p = 0.023). While on AID, time in range (70–180 mg/dL) significantly increased compared to SAP ( p < 0.001), accompanied by a reduction in hyperglycemia ( p = 0.001). Conclusions: These results suggest that use of AID has a positive impact on glycemic outcomes in young children as well as sleep and diabetes‐specific quality of life outcomes in their parents.